Methods and Findings on Diet and Lifestyle Used to Support Estimation of Radiation Doses from Radioactive Fallout from the Trinity Nuclear Test. Issue 4 (October 2020) - Potischman, Nancy; Salazar, Silvia I.; Scott, Mary Alice; Naranjo, Marian; Haozous, Emily; Bouville, André; Simon, Steven L.
Abstract : Abstract: The Trinity nuclear test was detonated in south-central New Mexico on 16 July 1945; in the early 2000s, the National Cancer Institute undertook a dose and cancer risk projection study of the possible health impacts of the test. In order to conduct a comprehensive dose assessment for the Trinity test, we collected diet and lifestyle data relevant to the populations living in New Mexico around the time of the test. This report describes the methodology developed to capture the data used to calculate radiation exposures and presents dietary and lifestyle data results for the main exposure pathways considered in the dose reconstruction. Individual interviews and focus groups were conducted in 2017 among older adults who had lived in the same New Mexico community during the 1940s or 1950s. Interview questions and guided group discussions focused on specific aspects of diet, water, type of housing, and time spent outdoors for different age groups. Thirteen focus groups and 11 individual interviews were conducted among Hispanic, White, and Native American participants. Extensive written notes and audio recordings aided in the coding of all responses used to derive ranges, prevalence, means, and standard deviations for each exposure variable for various age categories by region and ethnicity. Children aged 11–15 y in 1940s or 1950s from the rural plains had the highest milk intakes (993 mL d −1 ), and lowest intakes were among 11- to 15-y-olds in mountainous regions (191 mL d −1 ). Lactose intolerance rates were 7–71%, and prevalence was highest among Native Americans. Meat was not commonly consumed in the summer in most communities, and if consumed, it was among those aged 11-15 y of age or older who had relatively small amounts of 100-200 g d −1 . Most drinking and cooking water came from covered wells, and most homes were made of adobe, which provided more protection from external radiation than wooden structures. The use of multiple approaches to trigger memory and collect participant reports on diet and other factors from the distant past seemed effective. These data were summarized, and together with other information, these data have been used to estimate radiation doses for representative persons of all ages in the main ethnic groups residing in New Mexico at the time of the Trinity nuclear test.